Trimalchio’s Astrology: Naïve Superstitions or Intentional Jokes? (Petr. Sat. 35. 1–5; 39. 5–12) - Keyer, Denis (Hyperboreus, 2014)
Trimalchio’s zodiacal forecasts in ch. 39 do not indicate his liability to astrological superstitions, being a set of intentional jokes similar to the handing out of the apophoreta in ch. 56. Likewise, the foodstuffs assigned to zodiacal signs in ch. 35 aim at exquisite culinary design and are not to be imputed to simple-minded occultism.